Upaya Pemulihan Pariwisata Yogyakarta pada Masa Pandemi Covid-19 - Wahyuni, Dinar (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2021)
The Covid-19 pandemic has paralyzed Yogyakarta's tourism sector. The number of tourist arrivals decreased significantly, followed by a downturn in hotel room occupancy rates. As a result, a number of hotels, restaurants and other tourism businesses have closed either temporarily or permanently. Many tourism industry workers have been laid off. This study examines efforts to restore Yogyakarta tourism during the pandemic, using a descriptive qualitative approach. Data were collected through interviews, focus group discussions with the Tourism Office, Health Office, the Indonesian Tourism Industry Association and academics in Yogyakarta. It was found that Yogyakarta's tourism recovery is still in the emergency response phase due to the ongoing pandemic. This phase begins with a matching fund approach in which local governments reallocate budgets to mitigation programs and identify impacts on tourism by forming an internal review team. Three strategies to accelerate tourism recovery are carried out through innovation, adaptation, and collaboration. Digital technology development innovations through the Visiting Jogja and Jogja Pass, institutional innovations with the Ngayogyakarta Tourism Synergy, optimizing the promotion of Yogyakarta's new normal tourism, virtual tours, event tourism business matching, and travel corridor arrangements. Adaptation is carried out through communication campaigns for health and safety protocols as well as the implementation of Clean, Health, Safety, and Environment (CHSE) in destinations and the tourism industry. Collaboration is carried out between the central and local governments, tourism actors, the Central Bank of Indonesia, and the private sector. The key to the success of tourism recovery efforts is access and communication between the government and tourism actors. AbstrakPandemi Covid-19 telah melumpuhkan sektor pariwisata Yogyakarta. Jumlah kunjungan wisatawan menurun secara signifikan, diikuti penurunan tingkat penghunian kamar hotel. Akibatnya, sejumlah hotel, restoran, dan usaha wisata lain tutup baik sementara maupun permanen. Pekerja industri pariwisata banyak yang dirumahkan. Penelitian ini mengkaji upaya pemulihan pariwisata Yogyakarta pada masa pandemi Covid-19, dengan pendekatan kualitatif deskriptif. Data dikumpulkan melalui wawancara dan diskusi kelompok terpumpun dengan Dinas Pariwisata, Dinas Kesehatan, Gabungan Industri Pariwisata Indonesia dan akademisi di Yogyakarta. Hasil penelitian menunjukkan bahwa pemulihan pariwisata Yogyakarta masih berada pada fase tanggap darurat karena pandemi Covid-19 masih berlangsung. Fase tanggap darurat diawali dengan pendekatan matching fund di mana pemerintah daerah merealokasi anggaran ke program mitigasi dan melakukan identifikasi dampak pada pariwisata dengan membentuk tim kajian internal. Tiga strategi mempercepat pemulihan pariwisata dilakukan melalui inovasi, adaptasi, dan kolaborasi. Inovasi pengembangan teknologi digital melalui Visiting Jogja dan Jogja Pass, inovasi kelembagaan dengan Sinergi Wisata Ngayogyakarta, optimalisasi promosi pariwisata new normal Yogyakarta, virtual tour, event tourism business matching, serta travel corridor arrangement. Adaptasi dilakukan melalui communication campaign protokol kesehatan dan keselamatan serta implementasi Clean, Health, Safety, and Environment (CHSE) pada destinasi dan industri wisata. Kolaborasi dilakukan antara pemerintah pusat dan daerah, pelaku wisata, Bank Indonesia, serta swasta. Kunci dari keberhasilan upaya pemulihan pariwisata adalah akses dan komunikasi antara pemerintah dengan pelaku wisata. Monitoring dan evaluasi penegakan hukum dalam penerapan protokol kesehatan juga mendukung upaya pemulihan pariwisata.